Gestión de calidad en la Empresa Bananakaliljr S.A.S en el cantón Puebloviejo en el período 2023. - Quinto Arana, Sujeidy Alejandra (2024)
This case study is based on the quality management of the company BANANAKALILJR S.A.S dedicated to the production and marketing of agricultural products, the main activity being the cultivation of bananas and is located in the Puebloviejo canton, as is known to all companies. They seek to increase their profits, which means that they are the result of increased sales, but at the same time they seek to satisfy demand and consumers, such as being better than the competition, generating an environment of socioeconomic well-being, in this sense. to try to improve the quality of the product to be marketed. Aiming to evaluate quality management in the company BANANAKALILJR S.A.S in the Puebloviejo canton in the period 2023 to determine its degree of competence. To carry out the development of the case study, a comparative and descriptive research design was implemented, the situation of the company is not good, because through the surveys of the workers, necessary information was obtained about the incorrect administration and not having a quality management system that helps facilitate processes in the different areas of the company, causes that have caused discomfort and annoyance to workers, such as the fact of not growing quality products causing a decrease in their usefulness and this has caused the competition to be better in quality and sales.